Pendampingan Pencegahan Stunting melalui Intervensi Gizi Spesifik di Desa Mekar Sari Kecamatan Tatah Makmur Kabupaten Banjar - Hafiz Ramadhan; Dyera Forestryana; Cast Torizellia; Muhtadi Muhtadi; Haryoto Haryoto; Suranto Suranto (Penerbit Goodwood, 2023)
Purpose: The aim of this community service is to prevent the occurrence and increase of stunting through assistance with specific nutritional interventions in Mekar Sari Village, Tatah Makmur District, Banjar Regency. Methodology: Prevention assistance was carried out through counseling and providing education and information to pregnant women, breastfeeding mothers, and mothers with toddlers. The implementation of activities was also carried out in stages, including on September 22, 2023, counseling was given and provision of nutritious food and vegetables, continuously on October 4, 2023, was carried out at the same time as Posyandu activities by providing counseling and intake of vitamins and protein (milk and eggs). Results: The results of community service showed that participants knew and understood stunting and the factors that caused it; however, prevention methods that were not implemented led to an increase in the stunting rate in Mekar Sari Village, reaching 11 children from examination data until October 2023. The results of this activity also showed an increase in participants’ understanding. Protein and vitamin intake is one way to prevent stunting. Limitations: This activity was carried out on only 32 target people, including pregnant women, breastfeeding mothers, and mothers with toddlers. Contribution: The counseling and assistance activities for the Mekar Sari Village community need to be carried out consistently because they contribute to increased awareness of health problems, especially stunting prevention, in order to reduce the stunting rate.